Update of the History of the Shakespeare First Folio - West, Anthony James (Library, 2024)
Abstract This update of the Shakespeare First Folio History (2001) volume by Anthony West gives selected events in the story of the First Folio since 2001, complementing the update of West’s Census volume in the previous issue of this journal.